Influence of pH on the growth and sporulation of microbial bio-input agents - Steffen, Gerusa Pauli Kist; Steffen, Ricardo Bemfica; Vieira, Frederico Costa Beber; Boeni, Madalena; Maldaner, Joseila (Disciplinarum Scientia | Naturais e Tecnológicas, 2026)
The use of microbial bio-inputs has become an increasingly widespread practice in agricultural systems. Considering the high variability of soil conditions and the fact that the success of microbial agents depends not only on their intrinsic efficiency but also on their ability to adapt to the environment into which they are introduced, it is essential to investigate the relationships between soil parameters and microorganisms. This study aimed to determine the influence of medium pH on the establishment, growth, and sporulation of three fungal species of the genus Trichoderma and the bacterium Azospirillum brasilense. In vitro assays were conducted to evaluate the effect of five pH levels on: (1) the sporulation of T. asperelloides, T. virens, T. harzianum, and A. brasilense; and (2) the mycelial growth rate and dry biomass production of T. asperelloides, T. virens, and T. harzianum. The experiments were performed under controlled temperature (25 ± 1 °C) and photoperiod (12 h) conditions in a completely randomized design arranged in a factorial scheme consisting of five pH levels (4, 5, 6, 7, and 8) and four microbial species. Medium pH significantly affected the growth and sporulation of the fungal isolates of the genus Trichoderma and the bacterium A. brasilense, demonstrating that each microorganism has a specific optimal pH range. The optimal pH range for sporulation of T. asperelloides, T. harzianum, and A. brasilense was between 4 and 5, whereas T. virens exhibited optimal sporulation under slightly higher pH conditions (5-6). Significant differences were also observed in the mycelial growth rate of the three Trichoderma species across different pH levels. These results demonstrate that medium pH is a determining factor for the functional performance of microorganisms used in bio-inputs and highlight the need to integrate edaphic and ecophysiological compatibility into strain selection strategies to maximize agronomic efficiency in agricultural systems.